Alat Pendeteksi Suhu Tubuh dan Wajah (Kebutuhan Bukti Kehadiran) Berbasis Data - Aan Febriansyah; Junialdi Saputra; Puspita Desvirati (Manutech : Jurnal Teknologi Manufaktur, 2022)
This research leads to the manufacture of presence tools by implementing a face recognition and detection system, and is equipped with body temperature measurements. In this study, for face detection and recognition, the Local Binary Pattern Histogram (LBPH) Algorithm and Haar Cascade of Classifier were applied. The algorithm's working system performs face detection and recognition quickly with the use of a webcam. The scope of this research is to conduct database preparation, training, detection, recognition, and face identification. For measuring body temperature using the MLX90614 Infrared temperature sensor, this temperature sensor utilizes infrared radiation, this sensor can automatically measure energy in infrared radiation which will become a temperature scale. The testing process carried out in this study uses 100 databases of facial images that will be read during the detection process. From the test results, the face detection and recognition system will work optimally at a distance of 30-100 cm from the Web cam. while the body temperature measurement system will be more accurate at a distance of 5-15 cm from the temperature sensor MLX90614.